Sinto and national heart of japanese people - Кaйыркен Т. З.; Атaбaевa Э. К. (Journal of Oriental Studies, 2018)
This article is dedicated to Sinto, its unique and harmonious coexistence with the other religions, such as Buddhism, Christianity and Confucianism. Considered the relationship between the government and Sinto and its use as the main ideological instrument. This article narrates the story, which tells, that throughout the history of the government in the most critical moment for the union of the nation and its revival of patriotic feelings, the authorities of the country utilised the main idea of Sinto – an idea about a divine origin of the nation. The historical periods are described: the formation of the state, restoration Meiji, postwar Japan and the time of the phenomenal economical growth in the country